2015
DOI: 10.1149/2.0081503jss
|View full text |Cite
|
Sign up to set email alerts
|

Voiding Phenomena in Copper-Copper Bonded Structures: Role of Creep

Abstract: In 3D integration industrial context, copper is widely favored over others metals as a bonding material for its exceptional electrical and mechanical properties. It has been already reported that directly bonded structures involving copper layers exhibit typical voids that drastically abound beyond 300 • C. In order to have a better understanding of the voiding process, we specifically designed structures involving materials and surfaces exhibiting different properties. These stacks underwent different bonding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…2(d)-(f) show the same three structures after an annealing of two hours at 400°C under nitrogen atmosphere. Following previous reported mechanisms [8], a vertical grain growth and voids are observed in the (i) Cu-Cu bonding structure ( Fig. 2(d)).…”
Section: Methodssupporting
confidence: 83%
“…2(d)-(f) show the same three structures after an annealing of two hours at 400°C under nitrogen atmosphere. Following previous reported mechanisms [8], a vertical grain growth and voids are observed in the (i) Cu-Cu bonding structure ( Fig. 2(d)).…”
Section: Methodssupporting
confidence: 83%
“…Various experimental studies including Hobbs et al [31], Wang et al [32] and Gondcharton et al [33]) have shown the presence of voids in copper material. Therefore, it is relevant to consider an example of copper material for the purpose of numerical illustration of theoretical results.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Therefore, it is relevant to consider an example of copper material for the purpose of numerical illustration of theoretical results. To illustrate the dependence of amplitude ratios of various reflected waves on the angle of incidence, impedance parameter and other material parameters, the following relevant physical constants of copper material are taken as in Chirita and Danescu [25] and Bucur [27], that is, For the above values of material parameters, the nonhomogeneous systems (32) and (33) Fig. 2 by solid lines, when impedance parameter Z = 0.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…This specific shape is due to the copper interdiffusion. In the case of non polished copper surface, the created voids are much larger but the bonding interface is also perfectly sealed as shown in [13].…”
Section: A Wafer-level Bondingmentioning
confidence: 96%